Technical performance of soccer teams according to match outcome at the 2019 FIFA Women`s World Cup - Kubayi, A.; Larkin, P. (International Journal of Performance Analysis in Sport, 2020)
The purpose of the study was to examine the technical performance variables between teams which won and lost matches during the 2019 FIFA Women`s World Cup tournament. The sample consisted of 48 games played during the tournament. Data were obtained from the InStat Scout platform. Results showed that winning teams performed significantly (p < 0.05) better than losing teams in terms of technical performance variables such as total passes, passing accuracy, ball possession, shots, shots on target, aerial challenges, ball recovery patterns, and set piece indicators. Losing teams made more tackles, lost the ball more often, and received more yellow cards than winning teams. The findings of the current study may assist soccer coaches in structuring their team tactics and coaching sessions to improve the chances of winning in women`s international soccer competitions.